Дослідження методів захисту систем відеоспостереження на базі стандарту wi-fi - Поповська, Є. О. (ХНУРЕ, 2023)
The given work is devoted to the modern methods of protection surveillance systems established based on wireless systems. The subject of the study is the means of protecting the video surveillance system based on Wi-Fi wireless technology. Conducting a comparative analysis of Wi-Fi protocols. The main methods of wireless network encryption RC4, AES analyzed. Security protocols such as WEP, WPA, WPA2, and WPA3 reviewed and analyzed. The main methods of wireless network encryption RC4, AES analyzed